Integrating Educational Psychology and Anti-Corruption Education through Local Wisdom: A Character-Building Model in Indonesian Madrasahs - Ni Luh Wayan Yasmiati; I Wayan Lasmawan; Ida Bagus Putu Arnyana; I Wayan Kertih; I Ketut Gading (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
This study examines the integration of educational psychology and anti-corruption education grounded in local wisdom as a strategic model for character development in Indonesian madrasahs, contributing to SDG 4, particularly targets 4.7 (education for sustainable development and global citizenship) and 4. a (safe, inclusive, and effective learning environments). The research responds to the persistent challenge of moral degradation among students and the limited availability of holistic, culturally responsive character education models. Employing a qualitative multiple case study design, the study was conducted at MTsN 1 and MTsN 2 Buleleng, involving 26 informants (principals, teachers, students, and parents) selected through purposive sampling. Data saturation was achieved when no new themes emerged across interviews, observations, questionnaires, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, including data reduction, thematic analysis, and verification. The findings demonstrate that integrating psychological principles (self-awareness, empathy, and positive reinforcement) with anti-corruption values (honesty, discipline, and accountability), contextualized through local wisdom such as Tri Hita Karana, significantly enhances students’ character formation. Observable outcomes include reduced cheating behavior, improved task responsibility, increased honesty in daily interactions, and greater participation in collaborative and social activities. Furthermore, the synergy among schools, families, and community cultural practices fosters a sustainable moral ecosystem that supports inclusive and value-based learning environments. This study offers a contextually grounded, scalable model for character education, with practical and policy implications for strengthening culturally responsive, values-based education aligned with global educational goals.